Long-term increase in rainfall decreases soil organic phosphorus decomposition in tropical forests. (December 2020) - Sun, Feng; Song, Chengjun; Wang, Mei; Lai, Derrick Y.F.; Tariq, Akash; Zeng, Fanjiang; Zhong, Qiuping; Wang, Faming; Li, Zhian; Peng, Changlian
Abstract: Increased rainfall may affect soil phosphorus (P) cycling in tropical forest ecosystems, yet the key biotic and abiotic factors that govern soil organic P transformations remain unclear. In this study, we conducted a long-term (7 years) rainfall manipulation experiment in the field to examine the effects of increased rainfall (+25%) in the wet season on soil P dynamics in a tropical forest. We found that an increase in rainfall in the wet season enhanced the maximum P adsorption capacity of forest soil as a result of a greater availability of soil organic matter and organic iron (Fe)/aluminum (Al) oxides. Newly formed stable ternary complexes between soil organic matter, metals (Mn, Mg and Ca) and P increased the surface adsorption of soil organic P. Moreover, the alkaline phosphomonoesterase (ALP) activity was reduced under our experimental treatment owing to a decrease in the abundance of both ALP-producing bacteria ( Bradyrhizobium and Methylobacterium being the dominant genera) and bacterivores ( Rhabditis and Acrobeloides ). Our findings demonstrated an overall negative impact of elevated rainfall in wet season on soil organic P decomposition in tropical forests through the enhancement of soil P adsorption capacity and the inhibition of soil ALP activities. Our results implied that a long-term rainfall increase in the wet season could increase soil organic P accumulation, which in turn further reduce soil P availability for plant uptake in the tropical forests. Highlights: Increased rainfall increased soil P adsorption capacity in tropical forest. Increased rainfall inhibited soil bacterial decomposition channel in tropical forest. Increased rainfall decreased soil organic P decomposition in tropical forest. Soil organic Fe/Al oxides and soil organic matter contributed to soil organic P adsorption.